1996
DOI: 10.1111/j.1475-097x.1996.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved gas exchange during exercise after weight loss in morbid obesity

Abstract: The aim of this study was to determine the effect of weight loss induced by 6 weeks very-low-calorie-diet (VLCD) and behavioural intervention on pulmonary gas exchange during exercise in non-smoking morbid obese (BMI>40 kg/m2) otherwise healthy patients. Seven obese patients underwent a maximal bicycle ergometer test with continuous analysis of expired air and arterial blood sampling before and after a mean weight loss of 18% (25.7 kg, range: 10-50 kg). Body mass index (BMI) decreased with weight loss from 46.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 9 publications
2
39
0
1
Order By: Relevance
“…Therefore, the literature demonstrates as a whole that the morbidly obese do not have poor pulmonary gas exchange during intense exercise. Our data presented in this study corroborate these findings [8][9][10][11] and extend to include measurements over a wide range of exercise intensities before and after 21 kg of weight loss.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the literature demonstrates as a whole that the morbidly obese do not have poor pulmonary gas exchange during intense exercise. Our data presented in this study corroborate these findings [8][9][10][11] and extend to include measurements over a wide range of exercise intensities before and after 21 kg of weight loss.…”
Section: Discussionsupporting
confidence: 92%
“…Correcting for core temperature changes throughout exercise is important because increases in temperature affect blood-gas measurements [12,13]. Nonetheless, the few studies that did not temperature-correct blood-gas data suggest that the mean PaO 2 in the morbidly obese at near maximal to maximal exercise is approximately 84 to 98 mm Hg and that the AaDO 2 is 11 to 25 mm Hg [8][9][10][11]. These studies show that, on average, the morbidly obese do not have poor pulmonary gas exchange during intense exercise.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies in pathological obesity demonstrated an improvement in gas exchange [7] as well as left-ventricular morphology and function during exercise after weight reduction [8].…”
Section: Introductionmentioning
confidence: 99%